Cost-effectiveness analysis of Chinese patent medicines for the treatment of postmenopausal osteoporosis in China - Wang, Cong; Lin, Xihan; Liu, Jinyu; Zhang, Yu; You, Ruxu (Frontiers in Public Health, 2025)
IntroductionEvidence indicates that Chinese patent medicines can significantly increase bone mass in patients with osteoporosis and alleviate symptoms associated with low bone density. Although the therapeutic effects of these two drugs have been compared both directly and indirectly, no economic-related studies currently exist. Therefore, this study aims to assess the cost-effectiveness of Xianling Gubao Capsules compared to Jintiange Capsules and non-treatment for postmenopausal osteoporosis from the perspective of Chinese healthcare providers.MethodsA Markov microsimulation model was employed to estimate the cost-effectiveness of the Xianling Gubao capsule and the Jintiange capsule in a hypothetical cohort of postmenopausal osteoporotic women aged 55 to 74 years with no prior history of fractures, over a treatment period of 6 months. Model parameters, including transition probabilities and costs, were derived from Chinese sources. Efficacy data for the treatments were obtained from two network meta-analyses. Outcomes were expressed as incremental costs per quality-adjusted life-year (QALY) gained. Sensitivity analyses were performed to ensure the robustness of the findings, with a cost-effectiveness threshold established at three times the Gross Domestic Product (GDP) per capita in China ($38,223) per QALY.ResultCompared to the control group that did not receive drug treatment, the preventive therapy using Chinese patent medicine significantly increased bone mineral density and reduced the probability of fractures across all age groups in the intervention group. The incremental cost-effectiveness ratios (ICERs) for the Jintiange capsule compared to the Xianling Gubao capsule ranged from $11,955 per QALY at age 55 to $9,711 per QALY at age 74, indicating that the cost-effectiveness of the Jintiange capsule improved consistently with age. Sensitivity analyses confirmed the robustness of the results across all parameter variations, with the annual cost of the Jintiange capsule identified as the most sensitive factor.ConclusionFrom the perspective of Chinese healthcare providers, preventive therapy using Chinese patent medicine, when compared to a control group that did not receive drug treatment, resulted in increased bone mineral density and a reduced probability of fractures across all age levels in the intervention group. Additionally, the Jintiange capsule appears to be a cost-effective treatment option for postmenopausal women with osteoporosis.